A globally exponentially stable position observer for interior permanent magnet synchronous motors. (March 2021) - Ortega, Romeo; Yi, Bowen; Vukosavić, Slobodan; Nam, Kwanghee; Choi, Jongwon
Abstract: The design of a position observer for the interior permanent magnet synchronous motor is a challenging problem that, in spite of many research efforts, remained open for a long time. In this paper we present the first globally exponentially convergent solution to it, assuming that the saliency is not too large. As expected in all observer tasks, a persistency of excitation condition is imposed. Conditions on the operation of the motor, under which it is verified, are given. In particular, it is shown that at rotor standstill – when the system is not observable – it is possible to inject a probing signal to enforce the persistent excitation condition. The high performance of the proposed observer, in standstill and high speed regions, is verified by extensive series of test-runs on an experimental setup.